Women's perception of humor in TV advertising and its effect on recall (Encuentros, 2021)
This article analyzes women's perception of humor in television advertising messages, emphasizing aspects such as remembrance, perceived humor, use of humor and elements associated with that remembrance. For this, a descriptive approach was used with an online questionnaire that collected the perception of 81 women about mentioned aspects. One of the most relevant findings is that there is a relationship between humour and remembrance and that there is greater remembrance when the woman is represented in the content of the advertising message.
Keywords: Humor, advertising, perception, woman, remembrance.